ENVIRONMENTAL MONITORING OF SOIL POLLUTION WITH UNUSED AND PROHIBITED CHEMICAL PLANT PROTECTION MEANS NEAR WAREHOUSES IN TERNOPIL REGION - Glovyn, N.M.; Pavliv, O.V. (Scientific Progress & Innovations, 2019)
The article presents the results of environmental soil monitoring on the territory near warehouse with prohibited and unused chemical plant protection means (CPPM), which were accumulated on the investigat-ed site near the disposal of these substances in the village of Vyshnivchyk in Ternopil region. The intensive development of industry and agricultural activities causes negative anthropogenic effect on the environment. Therefore, the purpose of the study was to conduct environmental monitoring of soil condition around the warehouse as an object of disposing prohibited and unused CPPM. It is important to inform the public about the problem of disposing unused and prohibited CPPM. Today, Ukraine has accumulated about 8,000 tons of obsolete CPPM. The problem of their disposal has not been solved. Many of the warehouses where they are stored are in bad condition. Poor storage conditions of toxic residues of unsuitable and unused CPPM lead to their penetration in water sources and air, resulting in the risk of poisoning people and animals. Warehouse facilities turned out to be a potential threat to ecosystems adjacent to the warehouse. Special attention in this work is paid to the disposal of toxic chemicals in the village of Vyshnivchyk, Terebovlia dis-trict, Ternopil region (the territory of “Denys K” farm). The burial ground of toxic chemicals near Vysh-nivchyk has been in existence for over 30 years. It was built in 1978 according to the standards of that time. Loose and liquid chemicals were dumped into the quarry. The problem is complicated because the burial ground has no owner. At present it is not known what kinds of poisonous chemicals are in the preserved bur-ial ground. According to the accompanying documents, about 465 tons of dichlorodiphenyltrichloromethane (dust), over 200 tons of hexachlorane, as well as 7 tons of mercury and arsenic-containing substance have been accumulated there. According to the results of the agrochemical examination, the soil is characterized by a slightly acid reaction (soil type - leached black soil, coarse, light loamy, salt pH = 5.9; humus − 3.6 %). Due to wind and water diffusions of agrochemicals (contamination scattering up to 30 m away from the warehouse was detected); near the warehouse the following substances were revealed: 2.4-D-amine salt (0.35), simtriazine − 0.01–0.05 mg/kg, HCG − 0.02−0.14; DDT − 0.03−0.10; metaphos was not found, but it was detected in the warehouse (0.19); chlorophos was not found, but detected in the warehouse (0.10) mg/kg. The productivity and stability of ecosystems is significantly degraded at a distance of up to 50 meters away from the warehouse which negatively affects the biogeochemical circulation of substances. Thus, the insignificant content of CPPM residues near the warehouse in the village of Vyshnivchyk is explained by the fact that CPPM were initially stored in special premises, but over the time (the warehouse was built in 1978, the containers are useless) they penetrate the soil outside the territory of the warehouse.